The Toxicity of Lead in Vulnerable Populations: A Critical Review - Karokatose, Tolulope; Adewumi, Oluwalosola (Journal of Science, Technology and Innovation Research, 2026)
This review critically synthesizes current scientific evidence on the sources, mechanisms and health impacts of lead exposure in high risk population. The toxicity of lead has always been a major concern in public health, particularly among vulnerable populations such as children and pregnant women. Its danger is heightened by the fact that it is a non-biodegradable heavy metal as it remains un-decayed in the earth surface for centuries. Exposure to lead occurs mainly through contaminated water, soil, food, and air, with children and women of child bearing age facing the highest risk due to developmental and physiological factors respectively. Of particular concern is endogenous exposure during pregnancy and lactation, as lead stored in bones for decades is released into the blood stream, crosses the placenta and affects fetal development. A systematic approach was used to gather relevant literature from databases such as Pubmed, Google Scholar and Web of Science. Findings show that lead exposure contributes to various health issues affecting women and children. The review provides evidence that will inform public health strategies and intervention to better protect these vulnerable groups from the risk of lead exposure.